Detection of chicken adulteration in beef via ladder-shape melting temperature isothermal amplification (LMTIA) assay - Yongzhen Wang; Borui Wang; Deguo Wang (Biotechnology & Biotechnological Equipment, 2022)
AbstractThe ladder-shape melting temperature isothermal amplification (LMTIA) is a newly developed technique with advantages of simple mechanism, easy primer design, quick turn-around time, high specificity, high sensitivity and short target sequence compared to the loop-mediated isothermal amplification (LAMP) technique. The objective of this research was to establish the LMTIA assay for detection of chicken in beef. The LMTIA primers targeting the prolactin receptor gene of Gallus gallus were designed, the LMTIA reaction system was optimized, the specificity and the sensitivity of the LMTIA assay were determined. Our results showed that the LMTIA assay was able to specifically detect 100 ng genomic DNA of Gallus gallus, without detecting the 100 ng genomic DNA of Anas platyrhynchos, Felis catus, Sus scrofa, Canis lupus familiaris, Bos taurus or Capra hircus. The sensitivity of the LMTIA assay was 100 pg genomic DNA of G. gallus. Furthermore, the LMTIA assay was able to detect the chicken adulterated in beef with ≥0.1% (w/w) detection limit (LOD). This study holds a promise for facilitation of the surveillance of the commercial adulteration of chicken in beef.